Electrical Conductivity Breakthrough Experiment and Immobile Water Estimation in Organic Substrates: Is R = 1 a Realistic Assumption?. Issue 9 (22nd September 2015) - Caron, Jean; Létourneau, Guillaume; Fortin, Josée
Abstract : Core Ideas: Breakthrough of NaCl in peat shows that R may differ from 1. Immobile water in peat is difficult to estimate because of NaCl sorption. Solute sorption in peat varies because of uncoiling of organic components. Measuring electrical conductivity (EC) in outflow breakthrough curves (BTCs) is an approach commonly used to define transport parameters because it is rapid, inexpensive, and reliable. Earlier work has raised questions regarding the assumption that the retardation factor may be set at R = 1 when using EC as a tracer in organic soils. This study investigates the breakthrough of a NaCl tracer in a peat–sawdust mixture leached with distilled water. The results show that in such system, R may significantly differ from 1 because of sorption of Na + and Cl − by peat with the R value estimated by batch experiments to reach 1.9 for Na + and 1.5 for Cl − . The sorption properties may vary during solute transport because of uncoiling of humic and fulvic components with decreasing ionic strength of the solution.